Species Richness and Birds Conservation Priority in Mount Rinjani Areas, Lombok - Gito Hadiprayitno; I Gde Mertha; Moh. Liwa Ilhamdi (Biosaintifika: Journal of Biology & Biology Education, 2016)
Mount Rinjani area on the island of  Lombok is unique in bioecology. It provides habitats for many species of birds, especially birds of Wallacea. Several studies  on birds in this area have been done, but the conservation priority of these birds has not been determined. Based on this condition, the purpose of this research is to determine the priority of birds conservation in mount Rinjani areas. Exploration about the spesies of birds was started from Senaru Village to Segara Anak Lake. Abundance of each bird species was estimated using point count. Data analysis to determine the conservation priority used indicators that consist of endemicity, population status, species threatened and species management. The results showed that the birds species in mount Rinjani  areas are composed of 32 species belonging to 20 families. Bird species that have high abundance were Amandava amandava (15.94%), Zosterops Montanus (15.70%), and Parus major (11.32%), while Ptilinopus melanospila and Anthus novaeseelandiae were in low abundance (0.23%). Analysis birds conservation priority  in mount Rinjani areas indicates that Otus jolandae has the highest score (65) and should be the first priority for the conservation, while Philemon buceroides and Gallus varius with the same score (60) are the second priority. How to CiteHadiprayitno, G., Mertha, I. G., Ilhamdi, M. L. (2016). Species Richness and Birds Conservation Priority in Mount Rinjani Areas. Biosaintifika: Journal of Biology Biology Education, 8(3), 270-277.